Pengaruh Kompetensi Akuntansi Dan Pengalaman Praktik Kerja Industri Terhadap Kesiapan Kerja Siswa Kelas XI Program Keahlian Akuntansi SMK Batik 2 Surakarta - Lutfitasari, Riana, Drs. Samian, M.M (2016)
Riana Lutfitasari / A210120041, Effect of Accounting Competence and Experience Work Practices Industry Against Class XI Student Work Readiness Skills Program Accounting SMK Batik 2 Surakarta academic year 2015/2016, Department of Accounting Education, the Faculty of Education, Muhammadiyah University of Surakarta, June 2016. This study aims to determine; 1) Effect of accounting competence on the job readiness of students, 2) Effect of industry experience working practices to the readiness of students' work, 3) Effect of accounting competence and experience of the industry working practices to the readiness of student work. This research is quantitative descriptive research by drawing conclusions through statistical methods. The population in this study is a class XI student of Accounting Program SMK Batik 2 Surakarta totaling 38 students and the sample is all population of 38 students. Necessary data obtained through questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, t-test, F, and the coefficient of determination (R2) and the partial determination coefficient (r2). The results of the regression analysis obtained regression equation: Y = 0,044 + 0,383X1 + 0,387X2. the equation shows that the job readiness is influenced by accounting competence and experience of industrial work practices. The conclusions drawn are: 1) Competence to job readiness accounting students can be accepted. This is based on multiple regression analysis (t test) note that tcount > ttable namely 3.137 > 2.024 and the significance value < 0.05, namely 0.000 with partial determination coefficient of 23.98%. 2) Experience working practices of the industry on job readiness of students can be accepted. This is based on multiple regression analysis (t test) note that tcount > ttable namely 2.870 > 2.024 and the significance value < 0.05, namely 0.000 with partial determination coefficient of 21.05%. 3) accounting competence and experience of industrial work practices on the readiness of the students' work can be accepted. This is based on multiple regression analysis of variance (F test) note that Fcount > Ftable is 14.369 > 3.25 and a significance value < 0.05, namely 0.000. 4) Coefficient of determination (R2) of 0.451 indicates that the magnitude of the effect of accounting competence and experience of working practices of the industry on job readiness of students amounted to 45.1%, while the rest influenced by other variables.